MODEL PENGEMBANGAN PARIWISATA PEDESAAN SEBAGAI ALTERNATIF PARIWISATA BALI BERKELANJUTAN - Wirata, I Nengah (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2009)
The rapid tourism development in Bali has been a raising awareness of the importance of rural tourism industry as a means of sustainable rural development. The rural tourism constitutes a small industry for it primarily deals with small scale market, requires relatively small capital, utilizes local resources, and does not need sophisticated and expensive facilities. In rural tourism, there is a learning principle of nature in which the local community can also gain its benefits. Developing a tourism village can be a sensitive alternative because if it is not planned and managed properly, it can result in negative impacts on the existence of the local customs.